Interfaith Marriage: Subjectivity of the Judge in Determination of No. 454/pdt.p/2018 Surakarta District Court - Farid, Diana; Abdulah Pakarti, Muhammad Husni; Hendriana, Hendriana; Fathiah, Iffah (AL-ISTINBATH : Jurnal Hukum Islam, 2022)
This research discusses mixed marriage which is very controversial in society, even though most religions have prohibited the practice of mixed marriage. In Decree No. 454/Pdt.P/2018/PNSKt. The judge allowed the marriage of someone of a different religion, even though the Marriage Law clearly does not regulate and returns to the laws of each religion. HKI (Compilation of Islamic Law) prohibits the practice of interfaith marriage as stated in Article 40 letter c. This study aims to analyze the judge's considerations in granting or rejecting interfaith marriages with the applicable laws in the marriage law and KHI (Compilation of Islamic Law). The research method used is qualitative (library research) with a normative legal approach as an analytical tool to describe existing problems and gain insight. The results of this study indicate that the determination of interfaith marriages in Decision No. 454/pdt.p/2018, it is only the subjectivity of judges in interpreting Article 2 (1) of the Marriage Law and legalizing interfaith marriages which are in stark contrast to the Compilation of Islamic Law which has been in force in the Religious Courts in Indonesia.